Epidemiology of ovarian tumours in Northern India - A tertiary hospital based study - Sonia Puri; Veenal Chadha; A K Pandey (Wolters Kluwer Medknow Publications, 2018)
Introduction: Ovarian cancer is the leading cause of mortality of female gynaecological cancers and ranks seventh as the most common cancer worldwide. The increasing life expectancy has led to increase in its burden exponentially now even in developing countries but limited knowledge is there about the pattern of ovarian tumours. Objective: To determine the burden and describe the pattern of ovarian tumours in patients visiting GMCH. Material and methods: This epidemiological study is retrospective, descriptive hospital based study over five years. The data so collected was analysed using SPSS software. Results: Maximum number i.e 74(24.4%) of cases were in the age group of 50 to 59 years followed by 40 to 49 years. It is also seen that maximum number of cases i.e total of 65 registries were in the year 2013. Maximum number of cases were from the state of Haryana contributing to nearly 41% of total cases. Most of the cases could not be classified into four stages i.e they were categorized as unknown. Chemotherapy is the most commonly used treatment modality. Epithelial adenocarcinoma was the commonest histology subtype. Conclusion: Research should be aimed to find tools for screening and early diagnosis so that better therapeutic approaches can be designed to decrease the burden.